Análise espacial e temporal da expressão de genes relacionados ao metabolismo de lipídios em sementes de pinhão manso (Jatropha curcas L.) - Costa, Washington Luiz Gomes (2013)
The depletion of non-renewable energy such as oil, coal and natural gas, has stimulated the search for alternative sources of energy generation. In this context, physic nut (Jatropha curcas L.) has received special attention from researchers due to the presence of large amounts of oil in its seeds that can be converted into biodiesel. The objective of this study was to investigate the behavior of genes related to lipid metabolism during the development and germination of physic nut seeds. To accurately quantify the levels of gene expression by RT-qPCR, a selection of nine candidates for reference genes was performed. Our results showed that the GAPDH, UCP, ACT11, PP2A2 and CICLOF were the most stable genes during the development of the seeds. In germinating seeds, EF1-α, PP2A2, GAPDH, PUB3 and ACT11 were considered the most stable genes. To validate our findings with reference genes, we used the expression profile of the gene encoding the oleosin protein in which that was similar to those observed in the literature evaluated, indicating that they were suitable reference genes for data normalization by RT-qPCR. After obtaining these data, we performed a gene expression study by RT-qPCR of 20 genes involved in lipid metabolism. Our results revealed that the oleosin, β-ketoacyl-ACP Synthase I and II, thioesterase A and triacylglycerol lipase I genes, as well as other genes involved in lipid biosynthesis, achieved high expression levels in developing seeds. Acyl-CoA synthetase, thiolase and triacylglycerol lipase II, genes related to the degradation of lipids, showed high transcript levels in germinating seeds. The data obtained in this study contribute to the understanding of the metabolic pathways studied, providing subsidies for production of improved varieties of physic nut via genetic engineering.